Telemedicin enabled mobile pulse and blood pressure sensor - Cabrerizo, Ana Belén (Luleå tekniska universitet, EISLAB, 2000)
The last course, in the MSc in Electrical Engineering - Industrial Electronics, at Luleå University of Technology, is a project course. This year the goal was to produce a blood pressure and pulse measurement device. It was supposed to be used in elderly care since it is an inconvenience for them to have to go to a hospital just to measure their pulse and blood pressure. With this device these measurements can be made in their home environment which would help them to relax and make the measurement more accurate. A doctor would also be relieved of a lot of work since he would be able to run measurements parallel with other work and then come back to analyse them at a later point. It would also be easier to compare with previous measurements since it would be possible to store the measurements from each patient on "their own" homepage. The device is built around a Mitsubishi processor, M16C/62, and it communicates with Internet via Ethernet and Bluetooth. The report describes how the problems were solved and what was produced by the groups in the different areas such as the processor, electromechanics, user interface and Bluetooth. Antenna AB was our partner in working with this project. Godkänd; 2000; 20091001 (ysko)